الإعلام الديني ودوره في مواجهة أزمة التطرف (Comprehensive Journal of Science, 2025)
Praise be to God alone, and may peace and blessings be upon our Master Muhammad, his family, and his companions. Just as Islam is a religion of worship to the Almighty Creator, it is also a way of life, containing solutions to human problems. This aims to create an advanced Islamic environment that keeps pace with the developments of the age at all levels, in which Muslims serve as a role model. The contemporary crisis of religious extremism is nothing less than an intellectual crisis that threatens the lives of human societies. This is the idea behind the importance of this topic. Since the media is the easiest means of communication, the research was shed light on this topic through religious media, whose objectives stem from the principles of the message of Islam, which aims to reform thought and refine human behavior. The research objectives were: strengthening the role of religious media in addressing societal issues; renewing the mechanism of religious discourse through various media outlets; clarifying the complementary relationship between the message of the media, family upbringing, and the early stages of education; and clarifying the reality of religious extremism to develop mechanisms to contain and confront it. The problem of this research lies in the role played by religious media in addressing the extremism crisis. It is represented by two questions: What are the aspirations of religious media to address the extremism crisis in religion? And what are the challenges that hinder achieving this? Accordingly, the research had spatial limits represented by confronting the extremism crisis through religious media in Islamic societies in general and Libyan society in particular, and a temporal limit that was limited to the period following the Arab Spring revolutions. Thus, the work was based on the descriptive approach. The research was titled: "Religious Media and Its Role in Confronting the Crisis of Extremism - Aspirations and Challenges." The core of the research, after an introduction, included a preface that addressed the concept of religious media and its objectives, in addition to the concept of contemporary religious extremism and its most prominent characteristics. The research then focused on the role represented by aspirations. The first axis addressed the renewal of the approach to good preaching through questioning and discussion in a manner consistent with the addressee's personality and thought. It also emphasized the importance of spreading a culture of accepting others and clarifying who they are, creating a conducive environment for coexistence through meaningful and fruitful dialogue. The second axis followed, focusing on the challenges represented by the promotion of hate speech in various media outlets, in addition to the spread of the scourge of takfir. From this, the research concluded with a conclusion containing results and recommendations, the most important of which is that renewing religious discourse represented by good preaching has become an urgent necessity required by contemporary reality. This is part of the wisdom that Allah the Almighty has commanded in His saying: “Invite to the way of your Lord with wisdom.” In addition, incorrect family upbringing and corrupt social interactions, including their behavioral pathologies, result in a spirit of hatred in society. This poses a challenge to the message of religious media if this hatred turns into a discourse broadcast through various media outlets. This is compounded by the scourge of issuing judgments of disbelief by anyone, whether Harry, Dick, or Tom, which is a characteristic of religious extremism resulting from narrow-mindedness and neglect of reason in dealing with the texts of Islamic law. This requires certain recommendations, the most important of which is subjecting the religious material to be broadcast through the media to precise guidance from the religious authority in the state. This is to ensure that the discourse is free from the plagues of extremism and excommunication, which have become an intellectual crisis that has affected the preaching arena today.
Keywords: religious media, religious extremism, hate speech, excommunication.